2018
DOI: 10.1590/1981-863720180003000063408
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oral health conditions and risk factors for dental caries in patients with sickle cell disease

Abstract: Como citar este artigo / How to cite this article Medeiros MLBB, Mendes LL, Lopes SLP, Araújo EF, Silva IZG, Medeiros, et al. Analysis of oral health conditions and risk factors for dental caries in patients with sickle cell disease. RGO, Rev Gaúch Odontol. 2018;66(3):232-238. http://dx.ABSTRACT Objective To analyze the oral health conditions and risk factors for caries in patients with sickle cell disease. Methods An observational, cross-sectional study was conducted in the clinic of the Association of Person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…132,133 Thus, hyposalivation is related to dental caries. 134 Some systemic and metabolic disorders, such as Sjögren´s syndrome, medications, and head and neck irradiation, may cause salivary hypofunction, increasing the risk of caries. 91,135,136 The oral microbiota on clinically sound enamel surfaces comprises mainly non-mutans streptococci and Actinomyces.…”
Section: Biological Factorsmentioning
confidence: 99%
“…132,133 Thus, hyposalivation is related to dental caries. 134 Some systemic and metabolic disorders, such as Sjögren´s syndrome, medications, and head and neck irradiation, may cause salivary hypofunction, increasing the risk of caries. 91,135,136 The oral microbiota on clinically sound enamel surfaces comprises mainly non-mutans streptococci and Actinomyces.…”
Section: Biological Factorsmentioning
confidence: 99%
“…This study revealed an SCD prevalence of 5.7% (99 out of 1753 hospitalizations) [22]. Chronic hemolytic anemia, sickle cell crisis, susceptibility to bacterial infections, and slow tissue deterioration are the hallmarks of this condition [23]. SCD may present in various ways that might impact different body organs, including the kidney, lungs, musculoskeletal and cardiovascular systems, and so on [24].…”
Section: Sickle Cell Diseasementioning
confidence: 89%
“…On the other hand, SCD patients have a higher risk of dental complications due to changes in the dental structure, medications that contain sucrose, and increased susceptibility to infections, as found in an observational cross-sectional study by Medeiros et al in 2018. Poor dental hygiene is always a risk factor for SCD [23].…”
Section: Figure 3: Dental Manifestations Of Sickle Cell Diseasementioning
confidence: 99%